Encyclopedia of Statistical Sciences 2005
DOI: 10.1002/0471667196.ess0600.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Forecasting

Abstract: Bayesian forecasting encompasses statistical theory and methods in time series * analysis and time series forecasting * , particularly approaches using dynamic and state-space models, though the underlying concepts and theoretical foundation relate to probability modeling and inference more generally. This entry focuses specifically on time series and dynamic modeling, with mention of related areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…These results imply that our method provides a framework for more precisely estimating the CV of α tGH by smoothing the α tGH and eliminating temporal noise and cross-covariance dependencies. These results are consistent with studies that have shown when temporal correlation is ignored, estimators are often biased and variances are poorly estimated (West, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…These results imply that our method provides a framework for more precisely estimating the CV of α tGH by smoothing the α tGH and eliminating temporal noise and cross-covariance dependencies. These results are consistent with studies that have shown when temporal correlation is ignored, estimators are often biased and variances are poorly estimated (West, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…Forecasting the future of a dynamical system based on past noisy measurements and a system of dynamic equations is crucial for many scientific applications [40]. The most well-known of these applications is arguably weather forecasting [11].…”
Section: Bayesian Variational Forecastermentioning
confidence: 99%
“…The pair of sequences x n and y n yield a discrete-time, Markov state space model [27] conditional on the choice of parameters θ. The model is specified by the prior probability distribution of the state x 0 , which we denote as K 0 (dx 0 ), the dynamics of the state sequence x n , which is given by the Markov kernel…”
Section: Numerical Integration and State Space Modelmentioning
confidence: 99%